Buckling of pressurized spherical shells containing a through-thickness defect. (May 2020) - Yan, Dong; Pezzulla, Matteo; Reis, Pedro M.
Highlights: A thickness defect in a spherical shell can give rise to three distinct buckling regimes involving local buckling at the defect and global buckling of the entire shell. The resulting buckling behavior has been observed and analyzed through precision model experiments, finite element simulations, and a reduced axisymmetric shell model. The role of a thickness defect in dictating the buckling behavior of spherical shells is systematically studied over a wide parameter space, yielding quantitative results on buckling regimes and critical buckling conditions, related to the defect geometry. These features are entirely governed by the geometric parameters of the defect, and independent of the radius-to-thickness ratio of the shell. Graphical abstract: Abstract: We present a study on the pressure buckling of thin, elastic spherical shells containing a thickness defect. Methodologically, we combine precision model experiments, finite element simulations, and a reduced axisymmetric shell model. We observe qualitatively different buckling behavior by varying the geometry of the defect: either one buckling event or two events comprising local buckling at the defect and global buckling of the entire shell. We systematically analyze the loading path for the imperfect shell under prescribed pressure or volume change and identify three buckling regimes. We then explore a wide parameter space to study the dependence of the buckling regimes on the defect geometry, thus obtaining a phase diagram with quantitative relationships between critical buckling pressures and defect geometry. We find that the global buckling becomes insensitive to the defect beyond a critical value of its amplitude, and we demonstrate that the buckling regimes are governed by the three geometric parameters of the defect, namely its width, amplitude and the width of the transition region across the edge of the defect.